1994
DOI: 10.1215/03616878-19-2-361
|View full text |Cite
|
Sign up to set email alerts
|

Education and the Health Professions: Explaining Policy Choices among the States

Abstract: Recent calls for restructuring of the nation's health care system have highlighted the deficiencies in the current system of education for the health professions. Of particular concern are the dominance of specialization and hospital-based training and the tendency of new health care providers to settle in communities without substantial health needs. The states are the key actors in reforming health professions education, serving as a primary funding source for health professions schools, chief licensors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…24 We confirmed that, indeed, obligated physicians worked in counties with primary care physician-to-population ratios lower than their state's median county ratios more often than nonobligated physicians (37% vs. 11%, P Ͻ0.001).…”
Section: Communities and Patients Served By Physicianssupporting
confidence: 62%
“…24 We confirmed that, indeed, obligated physicians worked in counties with primary care physician-to-population ratios lower than their state's median county ratios more often than nonobligated physicians (37% vs. 11%, P Ͻ0.001).…”
Section: Communities and Patients Served By Physicianssupporting
confidence: 62%
“…10 States also recognized that their programs' smaller size make them more manageable, and their closer relationships with communities give them advantages in innovation and flexibility. 13,29,30 Indeed, the New Federalism doctrines in recent years have encouraged innovation by states as "policy laboratories." 27,29 State support-for-service programs also grew to fill a workforce void left when NHSC staffing dwindled in the late 1980s and when President Clinton's health care workforce reform proposals were defeated in the early 1990s.…”
Section: Commentmentioning
confidence: 99%
“…9 From 1985 through 1992, the pace of program growth quickened, with 35 states enacting legislation to create physician scholarships and similar programs. 12,13 Despite states' investments, little is known about their service-requiring programs. No national organization or central public agency monitors these programs.…”
mentioning
confidence: 99%
“…Recent examples include Hahn et al 1999 on tobacco policy; Kaskie, Knight, and Liebig 2001 on state dementia laws; Oliver 1999 and Morrisey and Jensen 1997 on insurance; Lear, Eichner, and Koppelman 1999 on the growth of school-based health centers; and Alexander and Succi 1996, Potter and Longest 1994, and Weissert, Knott, and Stieber 1994 on various provider issues. We believe this is the first such study of state legislative actions on this issue.…”
mentioning
confidence: 99%